Corporate digitalization in the european context: going one step further - Galeote Muñoz, María del Pilar (2023)
The digitalization of corporations is on the right path; however, the advantages sought by that process could be overshadowed by the disadvantages that come with any technological process. The aim of this work is to make a careful analysis of the framework set out by the lawmakers through Directive (EU) 2019/1151 of the European Parliament and of the Council, of 20 June 2019, amending Directive (EU) 2017/1132 as regards the use of digital tools and processes in company law, and, based on the principles governing corporate digitalization, take the analysis one step further, indicating where this issue should go in the future. Although technology helps corporations, its indiscriminate use in the corporate sphere could lead us to a European model of capital company that bears no resemblance to the one we have now. It is a process in which more advanced technology should be introduced progressively, in order to discover gradually how appropriate or not its adaptation is. This opens up a huge potential for modernizing corporate law that we should take advantage of – with caution and security – but to the fullest.